DAMPAK PENCABUTAN SUBSIDI BBM BAGI KEUANGAN NEGARA INDONESIA DALAM PERSPEKTIF GOOD GOVERNANCE - Julian Muhammad Hasan (Prima Center Indonesia, 2018)
In the discussion of this research is about the consistent implementation of fuel subsidies that resulted in the government must provide regular budget for domestic fuel sales such as kerosene, gasoline, avgas, avatur, and other types of fuel at low prices. With this policy, fuel subsidy by itself has an effect on the increase of fuel demand which at the same time increase domestic electricity usage. With the consistency of the fuel subsidy, both society and companies are allowed to purchase cheap domestic fuel prices by ignoring the scarcity factor of their natural resources. In 2014, the Indonesian government has revoked fuel subsidies. It has also passed the stage of consideration and has studied the policy plan to divert fuel subsidies from consumptive to productive. The policy will also have a positive impact and the negative impact of the revocation of subsidies. But with the way the policy is the most important is not out of the path of the concept of